Detrital zircon geochronology of the Grenville/Llano foreland and basal Sauk Sequence in west Texas, USA - Spencer, Christopher; Prave, A.R.; Cawood, P.; Roberts, N.M. (Geological Society of America, 2014)
U-Pb detrital zircon ages from Mesoproterozoic and Cambrian siliciclasticunits in west Texas (USA) constrain the depositional setting, provenance, and tectonic history of the region within a late Mesoproterozoic Grenville foreland basin and the early Paleozoic Sauk transgressive sequence. Two key units, the Hazel and Lanoria Formations, have detrital zircon age spectra dominated by detritus derived from the Grenville orogen (the Llano uplift anderoded equivalents), the ca. 1.4 Ga Granite-Rhyolite, and the ca. 1.7–1.6 Ga Yavapai/Mazatzal provinces. These data, combined with sedimentological data, permit interpreting those formations as the proximal and distal deposits, respectively, of a molasse shed into the Grenvillian foreland basin. Detrital zircons as young as ca. 520 Mashow that the Van Horn Formation, previously considered to be Precambrian in age,is no older than middle Cambrian. Further,the overall detrital zircon age spectrum of the Van Horn Formation is similar to that of the overlying Cambro-Ordovician Bliss Formation: both indicate derivation from sources that included the Colorado-Oklahoma aulacogen, Grenville, Granite-Rhyolite, and Yavapai/Mazatzal provinces.The similarities between the depositional history of the Van Horn and Bliss Formations lead us to conclude that the base of the Sauk Sequence in west Texas occurs at the base of the Van Horn Formation. Base-level rise associated with the Sauk transgression affected drainage patterns and sediment deposition along southwestern Laurentia some 20 m.y. earlier than previously assumed.